Manajemen Kepala Madrasah dalam Meningkatkan Kinerja Guru di MAS Persis Gunung Buntung Serang Banten - Mutmainah, Ina; Zulkarnain, Iskandar; Dewiyanti, Dewiyanti; Warisno, Andi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to find out and describe the management of the head of the Madrasah in improving the performance of MAS PERSIS Gunung Buntung teachers. This type of research is qualitative and descriptive research. The data sources in this study are (1) primary data, consisting of the head of the Madrasah, deputy head of the Madrasah, staff/employees, teachers; (2) Secondary data, obtained from literature research and documentation. The data collection methods in this study are observation, interviews, and documentation. The data analysis method is carried out by data processing (selecting, classifying, concluding results, and making data reduction). The results of the study show that the head of the Madrasah has carried out the stages of the management function well from the planning stage to supervision (controlling), but in its implementation sometimes there are obstacles, this is due to the lack of professional teachers, the lack of infrastructure, there are still teachers who do not understand the lesson plan and are reluctant to make the lesson plan, the lack of teacher awareness of discipline in teaching. Teachers' ability to evaluate learning has not been conferential, some still lead to cognitive aspects and psychomotor aspects are not paid attention to. Good management of Madrasah heads can improve teacher performance, both in planning, implementation and evaluation. This can be seen from the increase in teacher discipline in teaching, the learning tools owned by teachers are getting better and more complete